Low Light Availability Reduces the Subsurface Sediment Carbon Content in Halophila beccarii From the South China Sea - Premarathne, Chanaka; Jiang, Zhijian; He, Jialu; Fang, Yang; Chen, Qiming; Cui, Lijun; Wu, Yunchao; Liu, Songlin; Chunyu, Zhao; Vijerathna, Prabath; Huang, Xiaoping (Frontiers in Plant Science, 2021)
Eutrophication, dredging, agricultural & urban runoffs, epiphyte overgrowth and so on could reduce light availability for seagrass. This may affect “blue carbon” stocks in seagrass beds. However, little research is available on the effect of light intensities on carbon sequestration capacity in seagrass beds, especially the small-bodied seagrasses. The dominant seagrass Halophila beccarii, a vulnerable species on the IUCN Red List, was cultured in different light intensities to examine the response of vegetation and sediment carbon in seagrass bed. The results showed that low light significantly reduced leaf length and aboveground biomass, while carbon content in the both aboveground and belowground tissues were not affected. Low light reduced both the aboveground biomass carbon and the total biomass carbon. Interestingly, while under saturating light conditions it was similar between subsurface and surface carbon content, under low light conditions, subsurface sediment carbon was significantly lower than surface content. The reduction of subsurface sediment carbon might be caused by less release flux of dissolved organic carbon from roots in low light. Taken together, these results indicate that reduced light intensities to which these meadows are exposed to, will reduce carbon sequestration capacity in seagrass beds. Measures should be taken to eliminate the input of nutrients onto seagrass meadows and dredging activities to maintain the “blue carbon” storage service by enhancing light penetration into seagrass.